EDUCATIONAL SUPERVISION IN IMPROVING TEACHER PROFESSIONALISM - Sayed Aulia (CV Naskah Aceh, 2024)
Educational supervision is coaching in the form of guidance or any assistance from school leaders, which is aimed at the development of teacher leadership and other school personnel in achieving educational goals. This supervision is in the form of encouragement, guidance, and opportunities for the growth of teacher skills, such as guidance in efforts and implementation of reforms in education and teaching, choosing better teaching tools and methods, systematic assessment methods for the stages of the entire teaching process, and so on. This study aims to describe the role of the principal as a coordinator in improving teacher professionalism and describe the factors that influence educational supervision at MTsN 1 Bengkalis. This study. This study has limitations on the problem of supervision carried out by the principal, this study uses a qualitative approach with qualitative descriptive, the techniques used in collecting data are interview techniques, observation and documentation, the results of the study indicate the role of the principal's supervision a). the role of the principal's supervision as a coordinator: proper placement of teacher duties on the roster, direction using a loudspeaker every day, holding discussions together between teachers from various fields, b) supporting and inhibiting factors faced in supervision activities by the principal indicate that: 1) the supporting data is sufficient information, adequate teacher facilities and teachers who are easy to manage, 2) there are still teachers who feel afraid and even avoid when carrying out supervision activities, age factors that make teachers' understanding still slow, and managing time is still difficult.